Customer Relations Management sebagai Salah Satu Upaya Public Relations Perusahaan Jasa Perbankan Menciptakan Good Image - Prima Ayu Rizqi Mahanani (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2013)
This article deals with marketing trends in the 21st century is shifting from a transactional approach to the relational approach with focus on the fulfillment of needs, satisfaction, and pleasure affect business banking customers are very dependent on the customer. Map business services banking services fickle demands creativity public relations in providing the best service to its customers get a good image. Service concept using the service paradigm leading to cultivate the power of the customer based on the customer satisfaction-oriented, widely used by business banking services at this time. Paradigms that focus on how to provide services to the customer so that the customer was satisfied, beyond what can be given to something that is important and not to be underestimated. Skills to understand and fulfill customer expectations should be every company’s business philosophy of banking services and customer relationship management is a strategy